Benignly-fabricated crosslinked polyethylenimine/calcium-alginate fibers as high-performance adsorbents for effective recovery of gold. (10th April 2020) - Bediako, John Kwame; Lin, Shuo; Sarkar, Amit Kumar; Zhao, Yufeng; Choi, Jong-Won; Song, Myung-Hee; Wei, Wei; Reddy, D. Harikishore Kumar; Cho, Chul-Woong; Yun, Yeoung-Sang
Abstract: High-capacity crosslinked polyethylenimine (PEI)/Ca 2+ -Alginate fibers were fabricated as fast-kinetics adsorbents for application in gold recovery from urban mines. The benign protocols include strategic blending of PEI and alginate and extrusion into a mixture of CaCl2 and glutaraldehyde (GA) for simultaneous ionotropic gelation between the alginate and calcium ions, followed by chemical fixation of PEI into the Ca 2+ -Alginate matrix. Adsorption evaluation of the fabricated fibers showed remarkable gold uptakes surpassing 2300 and 1400 mg/g. The gold binding mechanisms were studied and elucidated with the aids of XRD and XPS as involving sequential electrostatic interaction and reduction by the amine, hydroxyl and aldehyde groups. The adsorption process was controlled by intra-particle diffusion mid-way towards equilibrium. The fibers were regenerated through adsorption-desorption cycles using 0.5 M thiourea/1 M HCl. The fibers demonstrated strong competiveness to existing adsorbents and have shown potentials for application as efficient adsorbents for recovery of gold from acidic solutions. Graphical abstract: Image 1 Highlights: High-capacity and chemically stable polymer-blended fibers were fabricated. The kinetics were good and gold uptake exceeded 2, 300 mg/g. Electrostatic and adsorption-reduction mechanisms played significant roles. Regeneration through adsorption-desorption cycles using acidified thiourea.